Androgen‐deprivation therapy, dementia, and cognitive dysfunction in men with prostate cancer: How much smoke and how much fire?. Issue 7 (16th January 2018) - McHugh, Deaglan J.; Root, James C.; Nelson, Christian J.; Morris, Michael J.
Abstract : Androgen‐deprivation therapy (ADT) remains the cornerstone of management for patients with metastatic prostate cancer. Although the toxicities of ADT are well established, there is increasing controversy surrounding the association between cognitive dysfunction and the receipt of ADT, with some evidence suggesting an increased risk of dementia. The authors conducted a literature search to identify pertinent clinical studies in this field. This general review outlines the key findings and discusses the relative strengths and weaknesses when drawing conclusions about the risk of cognitive dysfunction or dementia with ADT use. Cancer 2018;124:1326‐34 . © 2018 American Cancer Society . Abstract : Although contemporary retrospective studies assessing the risk of cognitive dysfunction or dementia in men who receive androgen‐deprivation therapy for prostate cancer are methodologically improved, limitations still exist that preclude any practice‐changing conclusions. Until prospective, randomized controlled trials are completed to address this, risk/benefit discussions with patients regarding androgen‐deprivation therapy should include the quality of the supporting data for any potential cognitive dysfunction or dementia risk.